Analyzing SD-WAN Deployment Challenges in the Retail Sector - Amod Darshane (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive case study analysis of a significant SD-WAN deployment failure within a large retail chain, offering critical insights into the challenges and complexities associated with network modernization in the retail sector. Through an in-depth examination of the implementation process, we identify key factors contributing to the failure, including inadequate pre-deployment assessment, poor vendor selection, overlooked security requirements, and difficulties integrating with legacy systems. The article employs a rigorous methodology, combining semi-structured interviews, document analysis, and on-site observations to provide a nuanced understanding of the technical, organizational, and human factors at play. By analyzing the consequences of the failed deployment, including increased operational costs, customer dissatisfaction, and reputational damage, we derive valuable lessons and best practices for future SD-WAN implementations. The article concludes with a discussion of risk mitigation strategies, the importance of tailored solutions, and long-term considerations for SD-WAN success in retail environments. This article contributes to the growing body of knowledge on SD-WAN adoption, offering practical guidance for retailers and IT professionals navigating the complexities of network transformation in an increasingly digital retail landscape.